The evolution of proton beam therapy: Current and future status - Tian, Xiufang (Mol Clin Oncol, 2018)
Proton beam therapy (PBT) has been increasingly used in a variety of cancers due to its excellent physical properties and superior dosimetric parameters. PBT may improve patient survival by improving the local tumor treatment rate while reducing injury to normal organs, which may result in fewer radiation-induced adverse effects. However, the significant cost of establishing and maintaining proton facilities cannot be overlooked. In addition, there has been significant controversy regarding routine application of this treatment in certain types of cancer. The challenges of PBT in the future mainly include the lack of basic clinical trials, unclear biological effects, immature imaging technology and miniaturization of imaging guidance. Overcoming these limitations may promote the rapid development of PBT. We herein provide an overview of the existing literature on the efficacy and toxicity of common oncological applications of proton beam therapy.